Relationships between Meteorological and other Variables and Bobwhite Spring Call Counts - Jeffrey G. Whitt; Kelly S. Reyna (National Quail Symposium Proceedings, 2022)
Accurate assessment of quail population trends is critical to the success of future conservation efforts. Financial considerations and time constraints often limit population trend estimates to indices, the most common of which are spring call counts and autumn covey counts. While all indices have limitations and caveats, spring call count data specifically possess variability that makes them ill-suited for detecting fine-scale trends. However, because spring call counts record calling males and are relatively easy to conduct, they are assumed to represent an index of breeding potential and produce the most data per unit cost. Here, we examine their variability, comparing the number of male northern bobwhites (Colinus virginianus; hereafter, bobwhite) calling and weather measurements recorded during >4,000 spring call counts conducted May–July 2014–2017. The number of male bobwhites recorded per call count decreased >2 hours after sunrise, as ambient temperatures increased, but increased with relative humidity. An increase in ambient noise was associated with recording fewer male bobwhites. There was no correlation with either wind speed/hour for 3 of 4 years, or with the Palmer Drought Severity Index. Comparing these results with other spring call counts in the literature highlights inconsistency in spring call count timing, and discrepancies between call count protocols and weather conditions that affect detection probability. We suggest incorporating these results into future call counts to more accurately assess bobwhite population trends.
Keywords: northern bobwhite; Colinus virginianus; call counts; whistle counts; population estimates; detection probability; Texas; quail abundance; population index; survey techniques